Leadership Education and Sustainable Development: Guidelines for Updating the Curriculum - Fortier, Denise; Viens, Nicolas (European Journal of Sustainable Development, 2018)
The sustainable business movement is likely the most important environmental movement in the world today. Therefore, universities must create an education system that does not destroy the biosphere. More specifically, given that businesses are powerful institutions, leadership and sustainable development (SD) should be an integral part of the business curriculum. The current lack of educational content on SD is linked to several issues. First, we need to approach leadership education from a sustaincentric paradigm, thereby moving away from emphasizing profitability at the expense of a healthy ecological, social, and economic context. Second, there remains a paucity of theoretical and practical tools for educating leaders to take on the SD challenge. Indeed, there is confusion regarding how leadership relates to successful implementation of environmental sustainability. In this paper, we outline some guidelines for leadership and SD. Accordingly, we acknowledge the fundamental complexity of SD and question the potential for contributions from biomimicry. We join the call for combining voices from multidisciplinary perspectives, including the physical and social sciences, as a necessary first step in our quest to take on the SD challenge and conclude that leaders must integrate a form of ‘shared leadership’ where followers are empowered to improve ecological innovation and find “green” alternatives. Keywords: Leadership Education, Leadership and Sustainable Development